Effect of Acute Gamma Irradiation on Curcuma alismatifolia Varieties and Detection of DNA Polymorphism through SSR Marker - Taheri, Sima (Hindawi Publishing Corporation, 2014)
The effects of eight different doses (0, 10, 20, 25, 35, 40, 60, and 100 Gy) of acute gamma irradiation on 44 (three varieties of Curcuma alismatifolia: Chiang Mai Red, Sweet Pink, Kimono Pink, and one Curcuma hybrid (Doi Tung 554) individual plants were investigated. Radiation sensitivity tests revealed that the LD(50) values of the varieties were achieved at 21 Gy for Chiang Mai Red, 23 Gy for Sweet Pink, 25 Gy for Kimono Pink, and 28 Gy for Doi Tung 554. From the analysis of variance (ANOVA), significant variations were observed for vegetative traits, flowering development, and rhizome characteristics among the four varieties of Curcuma alismatifolia and dose levels as well as the dose × variety interaction. In irradiated plants, the leaf length, leaf width, inflorescence length, the number of true flowers, the number of pink bracts, number of shoots, plant height, rhizome size, number of storage roots, and number of new rhizomes decreased significantly (P < 0.05) as the radiation dose increased. The cophenetic correlation coefficient (CCC) between genetic dissimilarity matrix estimated from the morphological characters and the UPGMA clustering method was r = 0.93, showing a proof fit. In terms of genetic variation among the acutely irradiated samples, the number of presumed alleles revealed by simple sequence repeats ranged from two to seven alleles with a mean value of 3.1, 4.5, and 5.3 alleles per locus for radiation doses of 0, 10, and 20 Gy, respectively. The average values of the effective number of alleles, Nei's gene diversity, and Shannon's information index were 2.5–3.2, 0.51–0.66, and 0.9–1.3, respectively. The constructed dendrogram grouped the entities into seven clusters. Principal component analysis (PCA) supported the clustering results. Consequently, it was concluded that irradiation with optimum doses of gamma rays efficiently induces mutations in Curcuma alismatifolia varieties.